Solution Of Linear Volterra – Stieltjes Integral Equation Of The Second Kind Using Generalized Midpoint Rule - A. Asanov; E. Hazar; M. Abdujabbarov (MANAS: Journal of Engineering)
In this study, the numerical solution of linear Volterra – Stieltjes equations of the second kind by using the generalized midpoint rule is established and investigated. The conditions on estimation of the error are determined and proved. One example is solved employing the proposed method.